A vajdasági magyar közösség politikai önszerveződése az 1990-es évek első felében - Bálint Csaba (2015)
The self-organization of the Hungarian community in Yugoslavia during the Yugoslav Wars and the formation of a democratic minority party system indicate the beginning of a long and presently still perceivable process, which personifies the striving of the Vojvodinian-based community after not just survival, but prosperity in their own homeland. The Democratic Fellowship of Vojvodina Hungarians, by forming a political party, means the first link in order to attain the appearance of Hungarian interests not only in the Yugoslavian parliament, but also at Hungarian and international levels. The party aimed to show up at every single level of the Serbian political system: on local government elections, on provincial elections and on general elections of the Republic of Serbia they tried to poll votes and form the strongest representation possible on the country's political stage. The selforganization of the Hungarian community is a cautionary tale since it can be reckoned as a success when it comes to the formation of the party and the acceptance of their own autonomy concept. This “cautionary tale” can be evaluated the most easily by the demonstration and recognition of the majority's political environment.
Keywords: Társadalomtudományok; Szociológia